Combating conflict with character - Cambridge Educational (Firm) (New York N.Y. : Cambridge Educational, 2011)
"Preparing students for a standardized test is a monumental task, but equipping them for social and interpersonal conflict is every bit as challenging. This five-part series helps young viewers navigate the dilemmas surrounding bullying, peer pressure, prejudice, and unresolved anger--with an additional program focusing especially on conflict management and resolution. Emphasizing character-building as a prime ingredient in overcoming conflict, the series uses no-nonsense dramatizations, candid 'school hallway' interviews, and expert commentary to define basic ideas, illustrate ways in which conflicts often play out, and ultimately present methods for diffusing them--based on honesty, awareness, and respect for others."--Publisher's web site.
[Disc 1]. Handling peer pressure (30 min.) -- [disc 2]. Overcoming prejudice (32 min.) -- [disc 3]. Dealing with bullying (32 min.) -- [disc 4]. Handling your anger and frustration (32 min.) -- [disc 5]. Managing conflict resolution (32 min.)
"Based on the Chelsea House book series Character Education, 9 volumes (2009)"
Instructor's guide for 5 parts can be downloaded at http://ffh.films.com/RelatedResourcesEC.aspx?TitleId=19338.
Casts: David Corenswet and others
Disc format: DVD, NTSC ; Region code: All.
In English with English subtitles and closed captioned.
Keywords: Conflict management; Interpersonal conflict in adolescence; Anger in adolescence; Frustration; Bullying in schools; Prejudices; Peer pressure in adolescence; Prevention